The Joint Commitment of Malukan Nationalist: The Revolutionary Axis Against the Dutch (NICA) Police Actions - Sem Touwe; Mohammad Amin Lasaiba (Paramita: Historical Studies Journal, 2025)
Abstract: This article examines the involvement of Malukan nationalists in the Indonesian National Revolution, particularly in confronting the attempted re-colonisation by the Netherlands Indies Civil Administration (NICA) during the 1945–1947 period. The research employs historical methods—including archival research, primary and secondary literature studies, and narrative and social historiographical approaches—to trace the dynamics of local resistance, reflecting ideological, political, and diplomatic strategies in defending independence. The findings show that Malukan nationalists—through organisations such as PIM, PRIMA, KRIM, and PARPIM—succeeded in forming networks of struggle that transcended regional, religious, and social class boundaries, rejected colonial co-optation, and voiced the sovereignty of the Republic of Indonesia in both national and international forums. This resistance was not only military-based but also emphasized dimensions of identity, national solidarity, and the influence of local intellectual elites. Within the theoretical framework of postcolonial nationalism and political settlement, this study demonstrates that various active and strategic local actors and contexts shaped Indonesian nationalism. Thus, this article challenges the dominant Java-centric historiography and offers an academic contribution to the global discourse on decolonisation, national integration, and the agency of local communities in building the postcolonial state. Abstrak: Artikel ini menelaah keterlibatan kaum nasionalis Maluku dalam Revolusi Nasional Indonesia, khususnya dalam menghadapi upaya rekolonisasi oleh Netherlands Indies Civil Administration (NICA) pada periode 1945–1947. Dengan menggunakan metode sejarah—meliputi penelitian arsip, kajian literatur primer dan sekunder, serta pendekatan historiografi naratif dan sosial—penelitian ini menelusuri dinamika perlawanan lokal yang mencerminkan strategi ideologis, politik, dan diplomatik dalam mempertahankan kemerdekaan. Hasil penelitian menunjukkan bahwa nasionalis Maluku, melalui organisasi seperti PIM, PRIMA, KRIM, dan PARPIM, berhasil membangun jaringan perjuangan lintas daerah, agama, dan kelas sosial, menolak kooptasi kolonial, serta menyuarakan kedaulatan Republik Indonesia di forum nasional maupun internasional. Perlawanan ini tidak hanya bersifat militer, tetapi juga menekankan dimensi identitas, solidaritas kebangsaan, dan pengaruh kaum intelektual lokal. Dalam kerangka teori nasionalisme pascakolonial dan penyelesaian politik, studi ini membuktikan bahwa berbagai aktor dan konteks lokal yang aktif serta strategis turut membentuk nasionalisme Indonesia. Dengan demikian, artikel ini menantang historiografi dominan yang berpusat pada Jawa serta memberikan kontribusi akademis terhadap diskursus global mengenai dekolonisasi, integrasi nasional, dan agensi komunitas lokal dalam membangun negara pascakolonial.